Studi Kasus Penanganan Pembiayaan Bermasalah di Baitul Maal wa Tamwil (BMT) Hubbul Wathon pada Masa Pandemi Covid-19 - Winda Hidayanti; Hesty Juan Kirana; Anisya May Yustitia; Harnum Widyaningrum; Tulasmi Tulasmi; Titania Mukti (ITB AAS INDONESIA Surakarta, 2021)
The research is a Case Study of Troubled Financing Handling at BMT Hubbul Wathon in the Covid-19 Pandemic. The research method uses a descriptive qualitative approach. In collecting data, researchers used interview techniques with BMT about policies to deal with the economic crisis during the Covid-19 Pandemic. BMT Hubbul Wathon Sumowono is one of the non-bank syari'ah financial institutions that issues a lot of financing products, such as Mudharabah, Musyarakah, Murabahah, and Ijarah financing. In providing financing to customers, an agreement is made in the BMT institution, in which there are several provisions that must be agreed upon by both parties. During the Covid-19 Pandemic, BMT Hubbul Wathon experienced a decrease in both savings, financing and installments. In the Covid-19 Pandemic as well, problematic financing at BMT Hubbul Wathon Sumowono increased by 5% when compared to the financing provided before the Covid-19 Pandemic. Therefore, this non-bank syari'ah financial institution issued several measures or policies including maintaining liquidity, restrictions in providing financing, and also by adding new customer members.